Three weeks with my brother - Sparks, Nicholas; Leyva, Henry; Sparks, Micah (New York Time Warner Audiobooks, 2004)
In January 2003, Nicholas Sparks and his brother Micah set off on a three week trip around the world. It was to mark a milestone in their lives, for at 37 and 38 respectively, they were now the only surviving members of their family. Against the backdrop of their trip, the Sparks brothers learn about loss, love, and hope.
Unabridged.
"A memoir"--Cover.
Includes an introduction read by Nicholas Sparks.
Produced and directed by Robert Kessler.
Read by Henry Leyva.
Issued also on cassette.
Keywords: Sparks, Nicholas; Sparks, Micah; 1900-1999; Brothers; Authors, American -- 20th century -- Biography; Talking books; Books on CD; Audiobooks; Compact discs; Biographies